2016
DOI: 10.1016/j.ijrobp.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Using [18F]Fluorothymidine Imaged With Positron Emission Tomography to Quantify and Reduce Hematologic Toxicity Due to Chemoradiation Therapy for Pelvic Cancer Patients

Abstract: Purpose The purpose of this prospective clinical trial was to determine the efficacy of FLT identified active bone marrow sparing for pelvic cancer patients by correlating FLT uptake change during and after chemoradiation therapy to hematologic toxicity. Methods Simulation FLT PET images were used to spare pelvic bone marrow using IMRT (IMRT BMS) for 32 patients with pelvic cancer. FLT PET imaging taken after 1 and 2 weeks of chemoradiation therapy and 30 days and 1 year after chemoradiation therapy was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 23 publications
1
41
0
1
Order By: Relevance
“…The extreme sensitivity of active pelvic bone marrow was recently demonstrated by McGuire et al. using [ 18 F]Fluorothymidine (FLT) imaging using positron emission tomography (FLT-PET) to identify active bone marrow before, during and after radiotherapy 29 . As little as a radiation dose of 4–5 Gy resulted in an approximately 50% decrease in FLT uptake and the suppression of bone marrow activity was measurable up to 1 y after radiotherapy, especially in pelvic cancer patients receiving radiation doses of more than 35 Gy 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extreme sensitivity of active pelvic bone marrow was recently demonstrated by McGuire et al. using [ 18 F]Fluorothymidine (FLT) imaging using positron emission tomography (FLT-PET) to identify active bone marrow before, during and after radiotherapy 29 . As little as a radiation dose of 4–5 Gy resulted in an approximately 50% decrease in FLT uptake and the suppression of bone marrow activity was measurable up to 1 y after radiotherapy, especially in pelvic cancer patients receiving radiation doses of more than 35 Gy 29 .…”
Section: Discussionmentioning
confidence: 99%
“…using [ 18 F]Fluorothymidine (FLT) imaging using positron emission tomography (FLT-PET) to identify active bone marrow before, during and after radiotherapy 29 . As little as a radiation dose of 4–5 Gy resulted in an approximately 50% decrease in FLT uptake and the suppression of bone marrow activity was measurable up to 1 y after radiotherapy, especially in pelvic cancer patients receiving radiation doses of more than 35 Gy 29 . Based on empirical experience, the use of daily fractions of 2 Gy to a total dose of approximately 46–50 Gy has evolved as a standard radiotherapy approach to control microscopic disease for most tumor types including cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BM-sparing techniques may be beneficial in improving tolerance to chemotherapy in the concurrent and potentially the adjuvant and salvage settings. McGuire et al (28) postulate that reducing the bone marrow volume receiving 10 or 20 Gy in total dose may delay the time to the occurrence of a hematologic toxicity event, which could result in the delivery of more chemotherapy. Also, we found that specific patient-related and treatment-related characteristics appear to play a role in the hematopoietic compensatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other modern techniques like magnetic resonance imaging (MRI), which provides an anatomical approach to imaging marrow distribution based largely on its relative fat and water content (Sebag, Dubois, Tabet, Bonato, & Lallemand, ), PET/CT more directly interrogates marrow function by exploiting specific physiologic pathways that mediate the distribution of certain positron‐emitting radiopharmaceuticals. In particular, PET/CT using 3′‐deoxy‐3′‐[ 18 F]fluorothymidine ( 18 FLT) has gained attention in recent years as a powerful tool to analyse marrow proliferation (Agool et al, ; Agool, Schot, Jager, & Vellenga, ; Ballegeer et al, ; Hayman et al, ; McGuire et al, ; McGuire, Menda, Boles Ponto, et al, ; McGuire, Menda, Ponto, et al, ; Menda et al, ). As a substrate for the pyrimidine salvage pathway of DNA synthesis, 18 FLT enters proliferating cells and becomes trapped due to phosphorylation by thymidine kinase 1 (TK1) (Salskov, Tammisetti, Grierson, & Vesselle, ; Shields et al, ).…”
Section: Introductionmentioning
confidence: 99%